Tinjauan Pelaksanaan Kerahasiaan Rekam Medis Di Puskesmas Kuranji Padang - Deni Maisa Putra; Rahmadhani (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
The medical record is also a documentation of the patient's condition and the contents of the medical record are medical secrets, especially in the storage of status in the filling room, which must be kept confidential, secure, and the medical record layout, whether it is appropriate or not by every health worker. The purpose of this study was to determine the Knowledge Review and Attitudes of Officers and Patients on the Confidentiality of Medical Record Files Primary Health Center at Kuranji Padang. This type of research is descriptive with a quantitative approach, the research sample is 90 patients and 4 health center officers using accidental sampling technique with data collection using questionnaires for patients and table cklis for officers. The results showed that there are still officers whose knowledge and attitude in maintaining the confidentiality of medical records (50%) or 2 people are still lacking and more than half of the knowledge (51.1%) and attitudes (52.2%) of patients towards maintaining the confidentiality of record files medical who do not understand and know. It can be concluded that Kuranji Primary Health Center, both patients and officers, is still lacking in maintaining the confidentiality of medical records. It is hoped that the head of the Primary Health Center will prepare Standard Operating Procedures (SOP) on medical records so that officers and patients know about medical records and about the confidentiality of medical records. In implementing the confidentiality of medical records, competent and professional medical record officers should know and understand more about medical records, participate in training and provide information to patients so that the confidentiality of medical records is maintained and can create good service.